Systematic review of ethnomedicine, phytochemistry, and pharmacology of Cyperi Rhizoma - Wang, Fengyou; Zhang, Shihao; Zhang, Jiaxu; Yuan, Fu (Frontiers in Pharmacology, 2022)
Cyperi Rhizoma (CR) is the dry rhizome of Cyperus rotundus L., a Cyperaceae plant. It has a long history of clinical medication and is known as the “holy medicine” of gynecology. CR smells sweet and bitter. It has the effect of soothing the liver and relieving depression, regulating qi, regulating meridian and relieving pain. It can be used to treat liver qi stagnation, chest pain, spleen and stomach qi stagnation, hernia pain, irregular menstruation and other diseases. At present, the main chemical constituents isolated from CR are volatile oil, flavonoids and terpenes. Modern pharmacological studies have shown that CR has a wide range of pharmacological activities, including antidepressant, hypoglycemic, antioxidant, anti-inflammatory, antipyretic and analgesic effects. In this paper, the botany, traditional application, phytochemistry, pharmacological effects, processing and other aspects of CR are reviewed. At the same time, the shortcomings of current research of CR are discussed in depth, and the possible solutions are put forward in order to find a breakthrough point for future research of CR.